2021
DOI: 10.1136/bmjopen-2020-047670
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for locomotion in incomplete human spinal cord injury (DBS-SCI): protocol of a prospective one-armed multi-centre study

Abstract: IntroductionSpinal cord injury (SCI) is a devastating condition with immediate impact on the individual’s health and quality of life. Major functional recovery reaches a plateau 3–4 months after injury despite intensive rehabilitative training. To enhance training efficacy and improve long-term outcomes, the combination of rehabilitation with electrical modulation of the spinal cord and brain has recently aroused scientific interest with encouraging results. The mesencephalic locomotor region (MLR), an evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 86 publications
0
13
0
Order By: Relevance
“…Treatment initiation in the early, subchronic phase after injury is more efficacious than in the fully chronic phase, and high-intensity training is crucial for long-term motor improvements that persist beyond the discontinuation of training. The effect of CNF-DBS depends on spared reticulospinal fibres and thus patients need to be selected accordingly in ongoing 43 and future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment initiation in the early, subchronic phase after injury is more efficacious than in the fully chronic phase, and high-intensity training is crucial for long-term motor improvements that persist beyond the discontinuation of training. The effect of CNF-DBS depends on spared reticulospinal fibres and thus patients need to be selected accordingly in ongoing 43 and future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“… 42 The potential of CNF-DBS to improve gait in non-ambulatory, chronic SCI patients is currently being investigated in a first in-man proof-of-concept trial ( https://clinicaltrials.gov , DBS-SCI, Identifier: NCT03053791). 43 In the present study, we first identified the safety window of stimulation parameters for CNF-DBS preserving controlled locomotor behaviour adapted to context in intact rats. We then show that the therapeutic effects of CNF-DBS on motor recovery appear progressively in the subchronic and chronic post-injury phases.…”
Section: Introductionmentioning
confidence: 99%
“…With a current clinical trial assessing MLR DBS in patients with incomplete SCI, 21 , 73 our findings reveal that the CnF offers a better and more reliable neurological target in comparison with the PPN for promoting recovery of motor and locomotor functions, strengthening the importance of evaluating the role of the CnF and especially glutamatergic neurons of the CnF in patients suffering from SCI. Our results also highlight the importance of continuing genetic dissection of functional microcircuits within the PPN in biomedical research.…”
Section: Discussionmentioning
confidence: 71%
“… 10 , 11 Although deep brain stimulation (DBS) in the PPN 7 or the CnF 8 can improve locomotor recovery in animal models of SCI, there are still questions about which neuronal population is the most efficient. With ongoing clinical trials aiming to assess DBS in the vicinity of the MLR of patients with incomplete SCI, 21 it is now urgent to gain a better understanding of how these distinct neuronal populations of the midbrain can contribute to and promote functional locomotor recovery after SCI.…”
Section: Introductionmentioning
confidence: 99%
“…But what does this mean for stimulation strategies to promote recovery from spinal cord injury? In the context of a current clinical trial that aims to use MLS-DBS following spinal cord injury, 8 this is important to define. Indeed, in rats, both CnF stimulation 9 and PPN stimulation 10 have been proposed to promote recovery, the latter when combined with local lumbar epidural stimulation.…”
Section: Main Textmentioning
confidence: 99%